Essays on voluntary disclosure information asymmetry, corporate governance and the securities market in Singapore. - Cheng, Eugene Chee Mun. (2008)
Three studies conducted to examine the market effects of increased voluntary disclosure as well as if firm disclosure policies improve with greater board independence in a Singaporean context.